‘Where all my bad girls at?’: cosmopolitan femininity through racialised appropriations in K-pop - Garza, Joyhanna Yoo (Gender and Language, 2021)
This article examines the polyvalence of racial(ised) representations in K-pop performances. The analysis of K-pop star CL’s (2013) song and video ‘Nappeun gijibae’ (‘The bad girl’) demonstrates how the artist projects an assertive femininity by embodying and localising the Bad Bitch: a sexually agentive figure of womanhood from US hip hop. CL’s use of African American English and conventionalised hip hop tropes helps resignify gijibae, a pejorative Korean term for women. By shifting between decontextualised styles invoking a different time and place, CL is able to build a kind of chronotopic capital that transforms fragmented styles into an empowered cosmopolitan femininity. However, although CL’s performance challenges Korean gendered norms in its use of local linguistic resources, her selective appropriations of US Black and Chicanx cultural signifiers reproduce narrow images of racialised femininities and reify a hierarchy of valuation along lines of gender and race.
Keywords: 2000 à aujourd'hui; K-pop; approches et analyses; appropriation culturelle; asie; chronotope; corps; corée du sud; cours; discipline; féminisme pop; lin2685; linguistique; performance de genre; premier cycle; périodes historiques; régions géographiques; sciences humaines; sofia; thématiques

La socialisation au féminisme des étudiant·es par les médias après #MeToo - Albenga, Viviane (Politiques de communication, 2021)
La socialisation au féminisme par les médias est un sujet dont l’acuité se renforce depuis le hashtag MeToo. Dans ce contexte, nous montrerons comment certains médias ont pu participer à la socialisation politique au féminisme d’étudiant·es. En replaçant ces effets socialisateurs par rapport aux socialisations familiales et nationales et à l’expérience des violences sexistes, l’article met en évidence que certains médias ont pu agir comme un processus de transformation de dispositions incorporées en dispositions politique. Nous analyserons ensuite les usages politiques de médias en termes de participation et d’information : d’une part, les usages des comptes Instagram féministes ; d’autre part, les effets de la combinaison d’informations politiques généralistes par les réseaux sociaux et Internet aussi bien que la radio et la télévision. Ce dernier usage diversifié est le fait d’étudiant·es avec un capital culturel plus élevé qui se réfèrent davantage à l’histoire du mouvement féministe et de sa production théorique.
Keywords: #metoo; 2000 à aujourd'hui; 2010-2019; 2020-2029; approches et analyses; cours; cyberféminisme; discipline; europe; france; féminisme pop; militance; pol4102; premier cycle; périodes historiques; régions géographiques; réseaux sociaux; sciences humaines; socialisation; sociologie; thématiques

La Conversation des sexes: philosophie du consentement - Garcia, Manon (Climats, 2021)
« L'affaire Weinstein et le mouvement #MeToo ont mis la question des violences sexuelles au premier plan. Depuis, le consentement renvoie naturellement au consentement sexuel et amoureux, envisagé comme un sésame de l'égalité entre femmes et hommes. Pourtant, il est bien difficile à définir, et soulève trois problèmes. Le problème juridique, bien connu de celles et ceux qui suivent l'actualité, peut être résumé ainsi : que faire pour que les cas de viol, d'agression et de harcèlement sexuels soient efficacement punis? Le deuxième problème est moral : comment penser des relations amoureuses et sexuelles qui ne soient pas fondées sur des normes sociales sexistes et inégalitaires? Enfin, le problème politique : comment ne pas reconduire les injustices de genre qui se manifestent dans les rapports amoureux et sexuels? La magistrale analyse du consentement que propose Manon Garcia revisite notre héritage philosophique, plongeant au cœur de la tradition libérale, mettant à nu ses impensés et ses limites. De John Locke aux théoriciennes féministes françaises et américaines, en passant par Michel Foucault et les débats sur la pratique du BDSM, c'est une nouvelle cartographie politique de nos vies privées que dessine cet essai novateur. Au terme de ce livre, il s'agira en somme, pour reprendre la formule de Gloria Steinem, d'« érotiser l'égalité » plutôt que la domination : en ce sens, le consentement sexuel, conçu comme conversation érotique, est sans doute l'avenir de l'amour et du sexe. »
Keywords: 2000 à aujourd'hui; approches et analyses; consentement; cours; discipline; droits des femmes*; europe; france; féminisme pop; justice sociale; metoo; phi4336; philosophie; premier cycle; périodes historiques; relations amoureuses; régions géographiques; sciences humaines; sexualité; thématiques

Pornography, feminist views of - Davis, Berta (The International Encyclopedia of Human Sexuality, 2015)
Feminist women's attitudes toward pornography are significantly polarized. Anti‐porn feminists have taken a position that pornography is degrading toward women, leads to distortion of healthy male‐female sexuality, leads to distorted images of the female body, increases male anxiety about sexual adequacy, sexual compulsivity, and increase violence toward women including rape and sexual harassment.
Keywords: approches et analyses; cours; discipline; féminisme anti-porn; féminisme pop; pornography; premier cycle; psychologie; ressource en ligne; sciences humaines; sex1911; sexualité; thématiques

Rethinking the effects paradigm in porn studies - McNair, Brian (Porn Studies, 2014)
It has been an assumption of most anti-pornography discourse that porn damages women (and children) in a variety of ways. In Porno? Chic!, the author interrogated this assumption by examining the correlation between the incidence of sexual violence and other indicators of misogyny, and the availability and accessibility of pornography within a number of societies. This article develops that work with a specific focus on the regulatory environment as it relates to pornography and sexual representation. Does a liberal regulatory regime in sexual culture correlate with a relatively advanced state of sexual politics in a given country? Conversely, does an illiberal regime, where pornography and other forms of sexual culture are banned or severely restricted, correlate with relatively strong patriarchal structures? A comparative cross-country analysis seeks to explain the correlations identified, and to assess the extent to which the availability of porn can be viewed as a causal or a consequential characteristic of those societies where feminism has achieved significant advances.
Keywords: LGBTQIA2+; analyse comparée; approches et analyses; communication; corps; cours; discipline; droits des femmes*; féminisme pop; histoire et politique; identités LGBTQIA2+; premier cycle; ressource en ligne; sciences humaines; sciences sociales; sex1911; sexualité; thématiques; violences; études culturelles

Porno? Chic!: how pornography changed the world and made it a better place - McNair, Brian (Routledge, 2013)
Porno? Chic! examines the relationship between the proliferation of pornography and sexualised culture in the West and social and cultural trends which have advanced the rights of women and homosexuals. Brian McNair addresses this relationship with an analysis of trends in sexualised culture since 2002 linked to a transnational analysis of change in sexual politics and sex/gender relations in a range of societies, from the sexually liberalised societies of advanced capitalism to those in which women and homosexuals remain tightly controlled by authoritarian, patriarchal regimes. In this accessible, jargon-free book, Brian McNair examines why those societies in which sexualised culture is the most liberalised and pervasive are also those in which the socio-economic and political rights of women and homosexuals have advanced the most.
Keywords: LGBTQIA2+; approches et analyses; communication; cours; discipline; droits des femmes*; féminisme pop; identités LGBTQIA2+; justice sociale; premier cycle; queer; sciences humaines; sciences sociales; sex1911; sexualité; thématiques; études culturelles

The feminist porn book: the politics of producing pleasure - Taormino, Tristan; Shimizu, Celine Parreñas; Penley, Constance; Miller-Young, Mireille (The Feminist Press at the City University of New York, 2013)
''This book brings together writings by feminists in the adult industry and research by feminist porn scholars. It investigates not only how feminists understand pornography, but also how feminists do porn - that is, direct, act in, produce, and consume this kind of 'industry'. With contributions by Susie Bright, Candida Royalle, Betty Dodson, Nina Hartley, Buck Angel, Lynn Comella, Jane Ward, Ariane Cruz, Kevin Heffernan, and more.''-- Fourni par l'éditeur.
Keywords: approches et analyses; arts; arts visuels et médiatiques; cinéma; communication; corps; cours; discipline; féminisme pop; féminisme pro-sexe; histoire et politique; premier cycle; ressource en ligne; sciences humaines; sex1911; sex1920; sexologie; sexualité; thématiques

Féminismes et pornographie - Courbet, David (L'attrape-corps, 2012)
Comment le féminisme peut se reconnaître dans la pornographie Objet de débats où la passion l'emporte bien souvent sur la raison, la pornographie semble à première vue s'opposer au féminisme. Or, les années 1980 voient éclore aux Etats-Unis un courant se définissant comme " pro-sexe " porté par des figures telles Annie Sprinkle ou Candida Royalle. Avec l'idée que la pornographie n'est pas systématiquement condamnable, la question suivante s'impose : peut-on parler de moyen d'émancipation ? La femme doit être libre de choisir la sexualité qui lui convient. Les films pornographiques conçus par des hommes et pour des hommes ne lui permettant pas d'obtenir une satisfaction complète, des réalisatrices, parmi lesquelles Erika Lust, Ovidie ou Emilie Jouvet, promeuvent une pornographie alternative où le plaisir féminin est - enfin - mis en exergue. Et brisent les standards pornographiques dominants ! Peu étudiées en France, les thèses défendues par les féministes pro-sexe n'ont encore que peu d'échos au sein du grand public. Basé notamment sur une dizaine d'entretiens de spécialistes et professionnels, ce travail cherche à élucider en quoi le féminisme peut se reconnaître dans la pornographie. Et inversement.
Keywords: approches et analyses; corps; cours; discipline; féminisme pop; féminisme pro-sexe; journalisme; premier cycle; science politique; science politique et droit; sciences humaines; sex1911; sexologie; sexualité; thématiques; travail

The Sexualisation of Culture? - Gill, Rosalind (Social and Personality Psychology Compass, 2012)
This article examines contemporary debates about the ‘sexualisation of culture’. It sets out the context for claims that Western societies are becoming more sexualised and it explores a number of competing perspectives about sexualisation. It then looks in more detail at the nature of claims about sexualisation as they emerge from the different disciplinary perspectives of Psychology and Media and Cultural Studies, contrasting the strengths and weaknesses of each, and raising criticisms of both. In a final discussion section, the article considers the usefulness or otherwise of the notion of ‘sexualisation’ as analytic category and points to the need to go beyond polarised positions. It advocates a psychosocial approach that takes seriously differences and power in considering the contemporary proliferation of ‘sexualised’ images, practices and media
Keywords: approches et analyses; communication; corps; cours; discipline; discours dominant; discours médiatique; féminisme pop; premier cycle; psychologie; ressource en ligne; sciences humaines; sex1911; sexualité; systèmes d'oppressions; thématiques; études culturelles

La chirurgie mammaire et l'esthétiquement correct : le sein et les médias - Le Louarn, S.; Le Louarn, C. (Annales de Chirurgie Plastique Esthétique, 2005)
Résumé Cet article discute en quoi les normes du sein esthétiquement correct, les caractéristiques physiologiques du sein, l'allongement de la durée de vie et les possibilités de la chirurgie esthétique influencent la demande de modification mammaire. Puis il examine comment le sujet des modifications mammaires est traité dans différents médias : presse écrite (notamment féminine), documentaires et spectacles de téléréalité. Il constate un paradoxe entre d'une part, un contexte social qui durcit des normes, encourage la quête du bien-être et la réalisation de soi et prône la tolérance et, d'autre part, la réalité d'un certain déni du droit des femmes à choisir leur apparence mammaire. L'article tente de décrypter les obstacles historiques, philosophiques, sociaux, religieux et idéologiques impliqués. Enfin, il propose une nouvelle grille de lecture du positionnement d'un individu par rapport à la chirurgie esthétique selon deux axes : le « Faire » et le « Dire ». Cette grille pourra aider le chirurgien plasticien à mieux décoder la demande de chaque patiente, pour mieux la satisfaire.
Keywords: 1900-1999; 1990-1999; 2000 à aujourd'hui; 2000-2009; approches et analyses; corps; corps féminin; cours; discipline; discours médiatique; esthétique; europe; france; féminisme pop; hétérosexisme; occident; premier cycle; périodes historiques; régions géographiques; santé; sciences humaines; soc2051; sociologie; systèmes d'oppressions; thématiques

Pornography, Women and Feminism: Between Pleasure and Politics - Ciclitira, Karen (Sexualities, 2004)
This article draws on a qualitative research study which set out to explore women’s experiences and views of pornography within the broader context of conflicting feminist positions on pornography. The research methodology posed an implicit criticism of the kind of ‘findings’ familiar from mainstream psychological research: semi-structured interviews were conducted with women from diverse backgrounds in the UK, and feminist theory and discourse analysis were used to inform interpretation of their accounts. Although the question of feminism was not explicitly raised by the interviewer, it emerged as a recurrent theme in interviews, with interviewees suggesting that the feminist anti-porn stance in particular has influenced their perspective on pornography. Their accounts show that women’s experiences are variegated, individual and complex, and that discourses of pornography and feminism may be negotiated in unpredictable ways.
Keywords: 2000 à aujourd'hui; 2000-2009; approches et analyses; cours; discipline; europe; féminisme pop; pornographie; premier cycle; psychologie; périodes historiques; recherche qualitative; ressource en ligne; royaume-uni; régions géographiques; sciences humaines; sex1911; sexualité; thématiques

Pornography embodied: from speech to sexual practice - Mason-Grant, Joan (Feminist constructions, 2004)
What does it mean to conceptualize pornography as a material practice rather than as speech? Mason-Grant argues that this idea, fundamental to the work of Andrea Dworkin and Catharine MacKinnon, has been obscured in legal wrangling and political polarization over their civil ordinance. Within the arena of legal argument, where the principle of free speech holds sway for progressive thinkers, their analysis of pornography is rendered, at worse, an apology for censorship and, at best, an argument about the social force of speech, rather than recognized as a fundamental challenge to the very idea of pornography as speech. In this book, Mason-Grant first shows how the persistent 'speech paradigm' inevitably obscures the innovative core of the Dworkin-MacKinnon critique of mainstream pornography. She then develops an alternative 'practice paradigm' that critically engages their analysis, capturing and extending its core insights about the role of pornography in sexual practice. Drawing on phenomenology of the lived body, this alternative paradigm provides a way of re-thinking how the pervasive use of mass-market heterosexual pornography contributes to the cultivation of an embodied and tacit sexual know-how that is subordinating, and raises important questions about alternative materials produced and used by sexual minorities. In her conclusion, Mason-Grant considers the implications of her analysis not for law, but for a critical pedagogy in youth sexuality education.
Keywords: approches et analyses; corps; cours; discipline; discours dominant; féminisme pop; hétérosexisme; militance; patriarcat; philosophie; phénoménologie; premier cycle; pédagogie; sciences humaines; sex1911; sexisme; sexualité; sofia; systèmes d'oppressions; thématiques

The trouble with nature: sex in science and popular culture - Lancaster, Roger N. (University of California Press, 2003)
Roger N. Lancaster provides the definitive rebuttal of evolutionary just-so stories about men, women, and the nature of desire in this spirited expose of the heterosexual fables that pervade popular culture, from prime-time sitcoms to scientific theories about the so-called gay gene.
Keywords: LGBTQIA2+; anthropologie; approches et analyses; cours; discipline; féminisme pop; genre; identités LGBTQIA2+; lit4700; premier cycle; queer; ressource en ligne; sciences humaines; sexualité; soc2014; thématiques; études culturelles

Carnal appetites: food, sex, identities - Probyn, Elspeth (Routledge, 2000)
n Carnal Appetites, Elspeth Probyn charts the explosion of interest in food - from the cults that spring up around celebrity chefs, to our love/hate relationship with fast food, our fetishization of food and sex, and the impact of our modes of consumption on our identities. 'You are what you eat' the saying goes, but is the tenet truer than ever? As the range of food options proliferates in the West, our food choices become inextricably linked with our lives and lifestyles. Probyn also tackles issues that trouble society, asking questions about the nature of appetite, desire, greed and pleasure, and shedding light on subjects including: fast food, vegetarianism, food sex, cannibalism, forced feeding, and fat politics.
Keywords: approches et analyses; care; corps; cours; discipline; féminisme pop; lit4700; premier cycle; ressource en ligne; sciences humaines; sciences sociales; sexualité; thématiques; études de genres

Body art: performing the subject - Jones, Amelia (University of Minnesota Press, 1998)
An examination of the social and cultural significance of body art by a major new voice. The past few years have seen an explosion of interest in body art, in which the artist's body is integral to the work of art. With the revoking of NEA funding for such artists as Karen Finley, Tim Miller, and others, public awareness and media coverage of body-oriented performances have increased. Yet the roots of body art extend to the 1960s and before. In this definitive book, Amelia Jones explores body art projects from the 1960s and 1970s and relates their impact to the work of body artists active today, providing a new conceptual framework for defining postmodernism in the visual arts. Jones begins with a discussion of the shifting intellectual terrain of the 1950s and 1960s, focusing on the work of Ana Mendieta. Moving to an examination of the reception of Jackson Pollock's "performative" acts of painting, she argues that Pollock is a pivotal figure between modernism and postmodernism. The book continues with explorations of Vito Acconci and Hannah Wilke, whose practices exemplify a new kind of performance that arose in the late 1960s, one that represents a dramatic shift in the conception of the artistic subject. Jones then surveys the work of a younger generation of artists -- including Laurie Anderson, Orlan, Maureen Connor, Lyle Ashton Harris, Laura Aguilar, and Bob Flanagan -- whose recent work integrates technology and issues of identity to continue to expand the critique begun in earlier body art projects. Embracing an exhilarating mix of methodologies and perspectives (including feminism, queer theory, philosophy, psychoanalysis, and literary theory), this rigorous and elegantexamination of body art provides rich historical insight and essential context that rethinks the parameters of postmodern culture.
Keywords: 1900-1999; 1950-1959; 1960-1969; 1970-1979; 1980-1989; 1990-1999; approches et analyses; art contemporain; arts; arts visuels et médiatiques; corps; cours; discipline; féminisme pop; har4600; histoire de l'art; performance; philosophie; postmodernisme; premier cycle; périodes historiques; queer; sciences humaines; sexualité; thématiques; théorie de l'art

Feminism and postmodernism - Ferguson, Margaret; Wicke, Jennifer (Duke University Press, 1994)
This collection of essays explores the significant agreements and tensions between contemporary feminist and postmodern theories and practices. Having brought enormous changes to conceptions of the body, identity, and the media, postmodernity compels the rethinking of many feminist categories, including female experience, the self, and the notion that "the personal is political." Feminist analysis has been equally important, though not always equally acknowledged, as a force within postmodernism. Feminist writings on subjectivity, master narratives, and the socioeconomic underpinnings of the master narrative of theory itself have been particularly influential. This volume traces the crossings and mutual interrogations of these two traditions into the arenas of cultural production, legal discourse, and philosophical thought. Multidisciplinary and international in their collective focus, the essays range from a study of Madonna as an Italian American woman who is revising the cultural meanings of an ethnic feminism to a unique interview with Mairead Keane, the national head of the Women’s Department of the Irish political party Sinn Fein. Turning the prism of postmodern feminism onto such diverse cultural objects as literary and literary critical texts, contemporary film, and music, these essays intervene in debates regarding technology, sexuality, and politics. Challenging modern feminisms to articulate their inescapable relation to postmodern society, this expanded edition of a special issue of boundary 2 also explores ways in which feminism can work as the cutting edge of a global postmodernism. Contributors. Salwa Bakr, Claire Detels, Margaret Ferguson, Carla Freccero, Marjorie Garber, Barbara Harlow, Laura E. Lyons, Anne McClintock, Toril Moi, Linda Nicholson, Mary Poovey, Andrew Ross, David Simpson, Kathyrn Bond Stockton, Jennifer Wicke
Keywords: amériques; approches et analyses; cours; discipline; fem1000; féminisme pop; irlande; philosophie; postmodernisme; premier cycle; régions géographiques; sciences humaines; troisième vague; états-unis; études culturelles

Unmarked: the politics of performance - Phelan, Peggy (Routledge, 1993)
Feminist film theory has made the psychic and political limitations of representational visibility abundantly clear. Yet the Left continues to promote visibility politics as a crucial aspect of progressive struggle. Unmarked examines the fraught relation between political and representational visibility and invisibility within both mainstream and avant-garde art. Suggesting that there may be some political power in an active disappearance from the visual field, Phelan looks carefully at examples of such absences in photography, film, theatre, the iconography of anti-abortion demonstrations, and performance art. A boldly specultative analysis of contemporary culture, Unmarked is a controversial study of the politics of performance. Situating performance theory within emerging theories of psychoanalysis, feminism, and cultural studies, Phelan argues that the non-reproductive power of performance offers a different way of thinking about cultural production and reproduction more generally. Written from and for the Left, Phelan's readings of the work of Robert Mapplethorpe, Cindy Sherman, Mira Schor, Yvonne Rainer, Jennie Livingstone, Tom Stoppard, Angelika Festa and Operation Rescue radically rethink the politics of cultural representation.
Keywords: amériques; approches et analyses; arts; cours; discipline; féminisme pop; har4600; histoire de l'art; histoire et politique; performance; philosophie; premier cycle; psychanalyse; ressource en ligne; régions géographiques; sciences; sciences humaines; sex2283; thématiques; états-unis

Un genre trouble: le féminisme, la pornographie, la réforme du droit et la thèse de la reproduction de l'ordre social - Lacombe, D. (Déviance et société, 1992)
L'étude de la campagne de criminalisation de la pornographie au Canada, dans les années 1980, pose un défi au savoir conventionnel qui s'est développé, en sociologie et en criminologie, sur la réforme du droit. Ce savoir est l'argumentation selon laquelle les réformes, en dispersant le contrôle social, ne font que légitimer le système sans le modifier fondamentalement. Afin d'éviter l'essentialisme de ce savoir, j'ai utilisé une approche reflexive qui pense la relation entre la réforme du droit et le pouvoir comme à la fois contraignante et facilitante. L'établissement d'un lien entre la pornographie et la déviance sociale n'apparaît pas comme une construction sociale unifiée, mais comme un terrain contesté dans lequel se produisent des rapports de pouvoir complexes, et une multiplicité de stratégies de résistance. C'est dans ce sens que la réforme apparaît comme un mécanisme générateur des pratiques.
Keywords: 1900-1999; 1980-1989; amériques; approches et analyses; canada; cours; criminologie; discipline; droit; féminisme pop; justice sociale; pornographie; premier cycle; périodes historiques; ressource en ligne; régions géographiques; science politique et droit; sciences humaines; sex1911; sexualité; sociologie; thématiques

L'Envers de la nuit: les femmes contre la pornographie - Lederer, Laura; Audy, Monique; Dufresne, Martin (Collection Les Entêtées, 1983)
Keywords: 1900-1999; amériques; approches et analyses; corps; cours; discipline; droit; féminisme pop; premier cycle; psychologie; périodes historiques; régions géographiques; science politique et droit; sciences humaines; sex1911; sexisme; sexualité; systèmes d'oppressions; thématiques; violences; états-unis